2009
DOI: 10.1177/0093854809344173
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Victim Gender, Defendant Gender, and Defendant Age on Juror Decision Making

Abstract: Mock jurors provided credibility ratings for a victim (12 years old) and defendant when victim gender, defendant gender, and defendant age (15 vs. 40 years old) were manipulated. Verdicts and sentence recommendations also were assessed. Higher guilt ratings were found for a male versus female defendant. Juror gender was examined as a covariate in the analyses. Female jurors rated the victim higher on accuracy, truthfulness, and believability than male jurors. Male jurors rated the defendant higher on reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
4
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 37 publications
5
54
4
3
Order By: Relevance
“…Contrary to the majority of literature in this area (Hetherton & Beardsall, 1998;Pozzulo et al, 2010;Rogers & Davies, 2007), we found no main effect of defendant gender on continuous verdict decisions. However, our path analysis demonstrated that defendant gender did predict perceptions of femininity, which in turn predicted the believability of the defendant's testimony, his or her likeability ratings, and the degree to which participants found the alibi to be compelling.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the majority of literature in this area (Hetherton & Beardsall, 1998;Pozzulo et al, 2010;Rogers & Davies, 2007), we found no main effect of defendant gender on continuous verdict decisions. However, our path analysis demonstrated that defendant gender did predict perceptions of femininity, which in turn predicted the believability of the defendant's testimony, his or her likeability ratings, and the degree to which participants found the alibi to be compelling.…”
Section: Discussioncontrasting
confidence: 99%
“…Much of this literature is focused on the effects of defendant gender in sexual abuse trials, and this research predominantly Downloaded by [Northeastern University] at 21:55 01 December 2014 suggests that mock jurors are more likely to convict male defendants than female defendants (Hetherton & Beardsall, 1998;Pozzulo, Dempsey, Maeder, & Allen, 2010;Rogers & Davies, 2007). However, outside this context, results are less consistent.…”
Section: Defendant Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, women are more empathic and emotionally sensitive (Eisenberg & Lennon, 1983). Accordingly, female jurors tend to sympathize more with the victim and have been found to be harsher in their verdict decisions in a variety of cases as compared with male jurors (ForsterLee, ForsterLee, Horowitz, & King, 2006;Pozzulo, Dempsey, Maeder, & Allen, 2010). This finding is particularly pronounced in cases involving child abuse, sexual assault, or IPV (e.g., Bagby, Parker, Rector, & Kalemba, 1994;Burke, Ames, Etherington, & Pietsch, 1990;Kern, Libkuman, & Temple, 2007;Quas, Bottoms, Haegerich, & Nysse-Carris, 2002).…”
Section: Juror Gender and Decision-makingmentioning
confidence: 99%
“…If the defendant is convicted, then s/he studies have documented a consistent effect of race of the defendant (for reviews see Mitchell, Haw, Pfeifer, & Meissner, 2005;Sommers, 2007) and/or the juror (e.g., Sommers & Ellsworth, 2000) on juror's verdicts. Likewise, research has also reported that these decisions can vary as a function of the sex of the juror (e.g., Hughes & Tuch, 2003;Murrell, Dietz-Uhler, Dovidio, Gaertner, & Drout, 1994;Pozzulo, Dempsey, Maeder, & Allen, 2010). Are similar effects observed with plea bargains?…”
mentioning
confidence: 97%